The Impact of technical education on the multidisciplinary training of high school students - Mera Zambrano , Katherine Estefanía (2025)
The objective of the research was to establish the effects of implementing technical education in the multidisciplinary training of high school students in Ecuador. A qualitative descriptive-correlational approach with a cross-sectional design was used. The population consisted of five teachers from the Francisco Daza Technical College in the Junín canton, Manabí province, selected using representativeness criteria. A structured survey with closed questions and an observation form on teaching practice were applied. The internal consistency of the questionnaire was evaluated using Cronbach's alpha coefficient. Sixty per cent of teachers consider that technical secondary education constitutes an early employment opportunity for students, while 80% perceive it as a mechanism for improving quality of life. However, 80% point out deficiencies in the current academic curriculum. It is concluded that technical education in secondary school has positive effects on youth employability and reduces unemployment levels, although it requires curriculum updates and improvements in educational infrastructure to optimise its educational impact.